PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENJUALAN OBAT KERAS TANPA RESEP DOKTER DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN (Studi Putusan Nomor 302/Pid.Sus/2023/PN Cjr) - Dwiana Prilly Larasati; Deny Guntara; Muhamad Abas; Mohamad ArdinSuwandi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines law enforcement mechanisms against the illegal distribution of drug solvents without medical prescription under Law No. 17 of 2023 concerning Health, analyzing the legal framework, enforcement challenges, and policy implications through Decision No. 302/Pid.Sus/2023/PN Cjr. The proliferation of illegal drug sales without medical prescription remains a persistent challenge in Indonesia, driven by factors including public demand for convenient access, cost considerations, and systemic weaknesses in pharmaceutical oversight, creating a critical gap between regulatory provisions and effective law enforcement implementation. Employing a normative legal research approach, this study analyzes positive law provisions, particularly Law No. 17 of 2023 concerning Health and relevant criminal law provisions, to evaluate the legal basis and enforcement mechanisms against unauthorized pharmaceutical distribution. Article 435 of Law No. 17 of 2023 provides a robust legal foundation for prosecuting both individual perpetrators and corporate entities involved in producing or distributing drug solvents without compliance with regulatory requirements. This study finds that Decision No. 302/Pid.Sus/2023/PN Cjr demonstrates the application of the ne bis in idem principle, ensuring defendants are not tried twice for the same criminal act. However, the case reveals significant structural weaknesses in the pharmaceutical regulatory and supervisory systems that continue to undermine effective enforcement. While law enforcement efforts against unauthorized drug distribution have commenced, current mechanisms remain insufficient without comprehensive systemic reform. The judiciary has correctly applied fundamental criminal law principles, yet enforcement success depends on strengthening digital oversight systems, harmonizing cross-sector regulations, and enhancing law enforcement capacity and digital forensics capabilities. This study contributes to legal scholarship by demonstrating the need for an integrated approach combining criminal prosecution, regulatory reform, and institutional capacity building, recommending that policymakers and law enforcement agencies prioritize modernizing pharmaceutical surveillance through digital systems, harmonizing regulations across relevant agencies, and developing specialized law enforcement units equipped with advanced forensic capabilities to effectively combat pharmaceutical crimes.